(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2025)
Traditionally, food fermentation has been practised as one of the food preservation methods and is still in vogue predominantly in Southeast Asian Countries. The methods of preparation and utilisation of different fermented fish products vary among the communities or regions of Northeast India. The Garo tribe of Meghalaya has a unique form of a fermented fish product known as “Na.kam su.a” prepared from Gangetic hairfin anchovy, Setipinna phasa. The proximate composition analysis of na.kam su.a, contained 32.54% crude protein followed by 36.82% moisture, 16.26% ash, and 13.44% lipid. The energy value of na.kam su.a was estimated as 419.6 kcal/100 g. The paper highlights the method of preparing and utilizing this traditional fish product of the Garo tribal community of Meghalaya in Northeast India.